T-cell receptor antibodies expression in benign and malignant cutaneous lymphoid infiltrates in comparison with T-cell receptor gene rearrangement and its diagnostic utility in borderline cases - Kamarádová, K; Hrochová, K; Salavec, M; Belada, D (Pathology, research and practice, 2020)
INTRODUCTION: Cutaneous T-cell lymphoid infiltrate can represent reactive lesion or a malignant T-cell lymphoma. However, clinical and histopathological appearance can overlap in both groups with a risk of misdiagnosis. Aberrant expression of T-cell markers is not always applicable and T-cell receptor (TCR) gene rearrangement is not always accessible and diagnosis in borderline cases can be challenging. AIMS: Several types of TCR antibodies are currently available with limited knowledge of their expression in different cutaneous lymphoid infiltrates. Aim of the study is a comparison of expression of TCR antibodies in benign and malignant lymphoid infiltrates and their utility in borderline cases. METHODS: Representative cases of reactive and malignant lymphoproliferations were collected. Separate group of lesions with borderline morphology was selected for comparison. Immunohistochemical expression of TCR-V-betaF1 (TCRBF1), TCR-C-beta1 (TCRJOVI.1), TCR gamma/delta (TCRGD) and TCR delta (TCRD) was performed in all cases. TCR gene rearrangement evaluation was performed in all cases using PCR BIOMED-2 assay. RESULTS: Benign lymphoid infiltrates were all negative in TCRD and TCRGD. Expression of TCRJOVI.1 was seen in 3/10 cases and TCRBF1 in one. T-cell lymphomas were positive for TCRBF1 and TCRGD in 60% and 30% of cases respectively. TCR gene rearrangement was confirmed in 90% of lymphoma cases. All benign lesions were polyclonal. Morphologically borderline lesions showed expression of TCRBF1 in 6/10 cases and TCR gene rearrangement in 4/10 cases. Re-evaluation of the cases and clinical correlation led to the change of the diagnosis and confirmation of T-cell lymphoma in 4/10 cases. CONCLUSIONS: Expression of TCRBF1 and TCR-gene rearrangement was significantly associated with malignant infiltrates. TCRBF1 positivity in borderline cutaneous lymphoproliferations can raise the suspicion of malignancy but confirmation by TCR gene rearrangement and careful clinical correlation is still advisable.
Keywords: senioři; diferenciální diagnóza; antigeny CD7; specificita protilátek; Lymphoma, T-Cell, Cutaneous; TCR rearrangement; Cutaneous lymphoproliferation; Receptors, Antigen, T-Cell, gamma-delta; Antibodies; protilátky; Male; Predictive Value of Tests; imunohistochemie; Middle Aged; mužské pohlaví; receptory antigenů T-buněk gama-delta; prediktivní hodnota testů; Adult; Cutaneous lymphoma; Immunohistochemistry; Antigens, CD7; ženské pohlaví; Humans; Lymphoproliferative Disorders; Inflammatory dermatosis; Skin; lidé středního věku; Antibody Specificity; Diagnosis, Differential; lymfoproliferativní nemoci; dospělí; genová přestavba T-lymfocytů; receptory antigenů T-buněk alfa-beta; kožní T-buněčný lymfom; Aged; Female; Receptors, Antigen, T-Cell, alpha-beta; kůže; lidé; Gene Rearrangement, T-Lymphocyte